Monetary and Fiscal Coordination in Small Open Economies - Worrell, Rupert (IMF Working Papers; Working Paper ;, 2000)
This paper is concerned with the design of institutional arrangements for low inflation in small open economies. In the real world of information asymmetries, uncertain expectations and changeable preferences, it is not enough to create an autonomous and publicly accountable central bank. In addition, the central bank and the treasury must work together on the design, implementation, monitoring and, when necessary, the revision of macroeconomic policy, and on providing the public with information on ongoing economic developments and interpretation of the macroeconomic strategy.